Franchising in South Asia: Past, present, and future developments. Issue 4 (1st October 2020) - Hussain, Dildar; Grünhagen, Marko; Panda, Swati; Hossain, Muhammad I.
Abstract: This study represents a first comprehensive overview of the state-of-the-art of the franchise industry in South Asia. The development of franchising in the seven South Asian countries of Bangladesh, Bhutan, India, the Maldives, Nepal, Pakistan, and Sri Lanka is outlined. A systematic overview of the franchise industry and its relatively short history in the region is created for each country, synthesizing economic and franchise infrastructure development. The study shows clear deficiencies across South Asia with regards to reliable legal regimes, specific franchise legislation and disclosure requirements, the availability of official data on franchising, and franchise education. Implications for policy makers and franchise academics conclude the analysis.